Penerapan nilai-nilai akhlak dalam kitab al akhlaq lil banaat dan pengaruhnya terhadap perubahan perilaku santri di Pondok Pesantren Al Islam Darul Falah Masaran Kabupaten Sragen - Anita Widhowati (At Turots: Jurnal Pendidikan Islam, 2023)
Research About the influence of the handbook in Teaching Activity is important. Whether an handbook have any influence or not. So as Kitab al Akhlaqu Lil Banaat, needs to be viewed, how much influence to fhe student's attitude.Tbis research will answer several questions, How the Pesantren Implement the Akhlaq to the female students? How much influence the reading the book al Akhlaqu lil banaat on female students at the Pesantren Al Islam Darul Falah, Masaran, Sragen?The metode used in this research is mixed research, both qualitative and quantitative. The Result of this research, the application of the akhlaq in the boarding school in several ways; habituation, reglulations and threats of sanction, and the unwritten rules suchas adab to the teachers. Meanwhile the moral of the students are very good in every aspect, akhlaq to Allah, Akhlaq to teachers, and akhlaq to friends. But there are the conflicts and the gossip ensued which led to a bad ratings. And the result of research on influence, it shows that the activity based on interest in reading book, have coefficients above 0,3 in All Aspects (Akhlaq to Allah, Akhlaq to teachers, and akhlaq to friends). but, there are lack corelations between the report value and the akhlaq of female students.The relationship between the value report with akhlaq to Allah (0,160), Akhlaq to teahers (0,126) and akhlaq to friends (0,035).this low coefficient shows a lack of apreciation of values during the learning. And this also shows the orientation of female students is only know of the meaningof the reading in the book al akhlaqu lil banaat, that wrietten in Arabic language.